2009
DOI: 10.3748/wjg.15.2908
|View full text |Cite
|
Sign up to set email alerts
|

Ampullary carcinoma: Effect of preoperative biliary drainage on surgical outcome

Abstract: AIM:To evaluate the influence of preoperative biliary drainage on morbidity and mortality after surgical resection for ampullary carcinoma. METHODS:We analyzed retrospectively data for 82 patients who underwent potentially curative surgery for ampullary carcinoma between September 1993 and July 2007 at the Singapore General Hospital, a tertiary referral hospital. Diagnosis of ampullary carcinoma was confirmed histologically. Thirty-five patients underwent preoperative biliary drainage (PBD group), and 47 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…This factor is poorly discussed in the literature, as only few authors have described PEBD as a possible risk factor influencing survival [10,30] . Abdullah et al [4] have similarly analysed influence of PBD on long-term survival in ampullary cancer patients; however, the authors did not reveal any survival differences in PBD and non-PBD groups.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This factor is poorly discussed in the literature, as only few authors have described PEBD as a possible risk factor influencing survival [10,30] . Abdullah et al [4] have similarly analysed influence of PBD on long-term survival in ampullary cancer patients; however, the authors did not reveal any survival differences in PBD and non-PBD groups.…”
Section: Discussionmentioning
confidence: 98%
“…Many treatment modalities have been applied to reduce jaundice preoperatively, thus preventing perioperative complications caused by cholestasis [4,31] . Regarding long-term outcomes some authors have shown negative influence of increased preoperative serum bilirubin [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Proponents advocate routine PBD in an attempt to reduce the incidence of hepatic dysfunction and perioperative complications in patients with obstructive jaundice, [28][29][30][31] while opponents consider that it does not significantly reduce postoperative complications and mortality, [32][33][34] can even result in major complications that can delay surgery and increase hospital costs, [35][36][37] and therefore should not be performed routinely. [13,[37][38][39][40][41][42][43][44][45][46][47][48] We have noted that almost all the above studies on the effects of PBD have the following limitations and methodological flaws: (i) most patient data were collected retrospectively, so there is a risk of selection bias; [44,47,48] (ii) in some studies, no distinction was made between different levels of biliary obstruction; [48][49][50] (iii) in many studies, no distinction was made between different types of operations; [36,44,48,51] (iv) often no distinction was made between different methods and durations of PBD; [45,47,49,52] and (v...…”
Section: Debate About Pre-operative Biliary Drainage For Obstructive mentioning
confidence: 99%
“…Despite the high rates of technical success with clinically relevant reductions of serum bilirubin levels and improvement in biliary stasis [42], a higher rate of stent‐related complications, including early stent occlusion, is seen in the preoperative drainage group compared to the direct surgical group. Pooled data from retrospective studies published over the past 5 years have shown similar rates of 30‐day mortality after pancreaticoduodenectomy in those who have undergone PBD and those who have not (Table 2) [28, 34, ]. Infectious complication rates were also similar in the two groups; however, the outcome measures have not been standardized and the lack of complete data on complications following preoperative drainage make direct comparisons difficult and biased.…”
Section: Introductionmentioning
confidence: 99%